The Decay of the Iranian Empire of the Seleucids and the Chronology of the Parthian Beginnings - Wolski, Józef
247 = Beginning of the Arsacid Era — 243 = Revolt of Andagoras — 239 = Diodotus Independent and King — 238 = Arsaces Invades Parthia.